Estimation of the efficiency of the Lima Stock Exchange (1990-2018) - Chávez Vargas, David Gonzalo (2021)
This paper shows the estimation of a restricted VAR model at the relation between the return of assets traded at Bolsa de Valores de Lima (Lima stock Exchange) and the economic fundamentals: aggregate consumption, exports, aggregate investment and real exchange rate. Using quarterly data we conclude that exists semi-strong efficiency in relation to the fundamentals, this could be an indicator of achievment of the functions of financial system in the domestic economy.